SOIL MICROBIAL POPULATION AND SELECTED ENZYME ACTIVITIES AS INFLUENCED BY CONCENTRATE MANURE AND INORGANIC FERTILIZER IN ALLUVIUM SOIL OF VARANASI - V. S. MEENA,; B. R. MAURYA,; R. VERMA,; R. S. MEENA,; G. K. JATAV,; MEENA, SUNITA KUMARI; R. MEENA,; S. K. MEENA, (The Bioscan, 2013)
A field experiment was conducted rabi season 2009-10 at Agricultural Research Farm, BHU, Varanasi, on alluvial soils to assessed the effects of concentrate organic manure and levels of inorganic fertilizers on microbial dynamics in alluvium soil. The maximum bacterial, fungal and actinomycetes population were recorded The total bacterial counts ranged from 42 × 105 cfu/g to 67×106 cfu/g, while the fungal density varied from 35 × 105 cfu/ g to 70 ×105 cfu/g and actinomycetes range 43× 105 cfu/g to 62×105 cfu/g. The highest microbial population were recorded during flowering stage of wheat with 100% NPK + 300 kg wellgrow soil/ha, while the lowest counts were recorded after harvest of wheat with 100% RDF. Highest soil enzymatic activity such as urease 300 µg UH g-1soil/h, dehydrogenase 235 µg TPF g-1 soil/day and phosphatase 78 ìg p-NP g-1 soil/h were observed with 100% NPK + 300 kg wellgrow grain/ha. Enzymatic activities were positively and significantly correlated with content of organic carbon.